Efisiensi Penggunaan Faktor Produksi pada Usahatani Padi Sawah di Subak Sembung Desa Peguyangan Kecamatan Denpasar Utara (Penerapan Analisis Stokastik Frontier) - NI MADE RIANA FITRI; DWI PUTRA DARMAWAN; I KETUT SUAMBA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Efficient Use of Production Factors on Wetland Rice Farming in Subak Sembung, Peguyangan Village, District of North Denpasar(Application of Frontier Stochastic Analysis) Subak Sembung is one of the subaks which get subsidy in the form of seed and fertilizer from the government. The existence of these subsidies allows wastefulness by farmers in the use of production factors. Based on this, a research was conducted that aimed to determine the efficiency of the use of production factors on rice farming in Subak Sembung. Random sampling technique was used to select the sample. The data collection in this study was conducted from October to November 2016. Researchers used the frontier production function and frontier cost functions estimated using the Maximum Likelihood Estimate (MLE) method. The results showed that rice farmers in Subak Sembung were efficient in using the production factor (cut-off value ? 0.7), but not in optimum efficiency condition at the frontier limit. Although farmers did not use production factors optimally, they had the opportunity to achieve optimal productive efficiency. Based on the result of significance with Fastilizer Stochastic analysis, it is known that only variable of land area that have a significant effect on paddy rice production.